AB0351 Biologic Tapering in Rheumatoid Arthritis: Initial Experiences in An English District General Hospital. (15th July 2016) - Trickey, J.; Holloway, C.; Robinson, H.; McDowell, J.; Andrews, S.; Jolliffe, V.; Joshi, A.; Rees, D.; Peall, A.
Abstract : Background: Biologics are effective therapies in the treatment of Rheumatoid arthritis (RA) 1 . However, they are expensive and may have potentially serious side effects including infection 2 . There is growing evidence that biologic doses may be tapered down in patients with well-controlled RA, and good disease control may be retained 3 . Objectives: To ascertain if biologic tapering in patients with RA retain good disease control when biologic doses are tapered down, in a small district general hospital rheumatology department. Methods: Patients taking biologics and with quiescent RA were selected prospectively on attendance to rheumatology follow up clinics, commencing in June 2015, and consented to participation in dose tapering. Eligible patients must not be taking corticosteroids. They must have disease remission for at least 2 years (defined as DAS28CRP <2.6). Alternatively, they may have disease remission for 12 months and no evidence of synovitis on ultrasound. Rituximab dose was decreased to one 1g infusion every 6 months. Infliximab, Abatacept and Tocilizumab infusion doses were reduced by 25%. Frequency was prolonged by 50% in subcutaneous TNF inhibitors. Patients were followed up at 6-monthly intervals with support from rheumatology help line in between for flares of disease. Results: Between June 2015 and January 2016, 25 patients with RA have had biologic doses tapered. 6 month follow up appointment data is currently available for 10 patients. One female patient was found to have active disease at 6 month follow up, and one male patient had a flare up 1 month before his clinic appointment, so both have reverted back to standard dose biologic. Mean DAS change for the 9 patients seen 6 months after dose tapering was +0.39 (-0.24: +2.03), which was skewed largely by the one female patient who had a flare at follow up. Median DAS change was +0.1. Mean GVAS before tapering was 29.8, and 33.7 at 6 month follow up. Mean CRP pre-tapering was 5.75 and at 6 months was 4.7. Two patients had a DAS 28 >3.2 at 6 months: one of whom had recent surgery which was felt to have contributed to disease flare so reduced dose Rituximab was continued. 6 out of the 9 patients had no swollen joints at 6 month follow up Conclusions: So far 2 out of 25 patients have needed to revert back to original dose of biologic after tapering, which is promising. 7 of the 9 patients followed up on tapering had static disease activity. This suggests that dose tapering can be successfully achieved in a majority of RA patients who have achieved disease remission. References: Callhoff J; Impact of biologic therapy on functional status in patients with rheumatoid arthritis – a meta-analysis; Rheumatology 53, 29; doi: 10.1093/rheumatology/ket266 Ding T et al; BSR and BHPR rheumatoid arthritis guidelines on safety of anti-TNF therapies; doi: 10.1093/rheumatology/keq249b Smolen JS et al; EULAR recommendations for the management of rheumatoid arthritis with synthetic and biological disease-modifying antirheumatic drugs: 2013 update; Ann Rheum Dis; doi: 10.1136/annrheumdis-2013-204573 Disclosure of Interest: None declared